Economic policy uncertainty and climate change evidence from CO2 emission - Benlemlih, Mohammed; Yavaş, Çiğdem Vural (2024)
In this paper, we study the relationship between Economic Policy Uncertainty (EPU) and carbon dioxide (CO2) emissions. Using an extensive dataset from 23 countries consisting of 6800 firm-year observations, we provide strong evidence that EPU increases firms' CO2 emissions. Our main inference is robust when using alternative measures of CO2 emissions and EPU, alternative econometric specifications and samples, and several approaches to control for possible endogeneity. In a set of additional analyses, we first show that a board's characteristics (i.e., board gender diversity and board independence) significantly moderate the studied relationship. Second, cross-country characteristics (i.e., government effectiveness, control of corruption, and democracy) seem important in the relationship between EPU and CO2 emissions. Our findings significantly contribute to the debate on firms' ethical responsibility in managing climate change and CO2 emissions.
Keywords: CO2 emissions; Climate Change; Economic policy uncertainty; Environmental Performance; Aufsatz in Zeitschrift